This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
The general formula for this one is: lo g x ( a ) − lo g x ( b ) = lo g x ( a ÷ b ) Therefore, inputting our values: lo g 5 ( 6 5 ) − lo g 5 ( 1 3 ) = lo g 5 ( 6 5 ÷ 1 3 ) lo g 5 ( 6 5 ÷ 1 3 ) = l o g 5 ( 5 ) Although this is the answer required, we can simplify this further by utilising the rule: lo g x x = 1 So: lo g 5 5 = 1 The Log subtraction rule is important to remember!